THE IMPROVEMENT OF THE JACK FRUIT DRAINING PROCESS - Thi Sen Nguyen; Igor Yurevich Aleksanyan; Roman Vakhaevich Mutsaev (Современная наука и инновации, 2022)
The description of the object of research, its properties and characteristics for its industrial processing is given. The current state and prospective directions of intensification of heat storage in the production of dry products and concentrates are analyzed. A rational scheme for radiation-convection drying is recommended for vegetable cut products.